2018
DOI: 10.21653/tjpr.453714
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fear of Movement in Patients With Rheumatoid Arthritis

Abstract: Purpose: Patients with rheumatoid arthritis (RA) frequently have experience difficulties during daily activities since decrease in upper and lower extremity functions. The aim of this study was to investigate the association between fear of movement and age, upper and lower extremity function and functional disability in patients with RA. Methods: A total of 88 patients (mean age: 56.01±11.51 years) with RA participated in the study. Disease activity was assessed using the Disease Activity Score in 28 joints (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Previous studies agree with the present results, such as Kinikli et al, where pain and function were considered as predictive factors to suffer from kinesiophobia [ 16 ]. Additionally, Luque et al, Bilgin et al and Luijsterburg et al [ 26 , 32 , 33 ] demonstrated an association between kinesiophobia and musculoskeletal pain (mainly in the shoulder, neck, and back).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies agree with the present results, such as Kinikli et al, where pain and function were considered as predictive factors to suffer from kinesiophobia [ 16 ]. Additionally, Luque et al, Bilgin et al and Luijsterburg et al [ 26 , 32 , 33 ] demonstrated an association between kinesiophobia and musculoskeletal pain (mainly in the shoulder, neck, and back).…”
Section: Discussionsupporting
confidence: 93%
“…However, there are a lack of studies related to kinesiophobia and foot and ankle involvement in patients with RA. Some previous studies examined the level of fear of movement in patients with RA through the TSK-17 but on a general level [ 16 ]. From another perspective, some previous studies have been published regarding the relationship between kinesiophobia and the following areas: upper limbs in osteoarthritis [ 17 , 18 , 19 ], osteoporosis [ 20 ], and knee and hip surgery [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the QuickDASH/PSFS change score and the SQK change score is moderate (> 0.30 and < 0.60). This hypothesis is based on previous studies showing that fear of movement scales correlates moderately with shoulder disability scores [47,48].…”
Section: Mic Assessmentmentioning
confidence: 99%
“…Korku kaçınma modelinin sonucu olarak ağrıyla ilgili korku, hareket korkusu ve kinezyofobi kavramları ortaya çıkmıştır (27). Literatürde kronik ağrılı bireylerde ve ağrılı diğer hastalıklarda kinezyofobi düzeyinin yüksek olduğu gösterilmiştir (28,29). Fakat PH'de kas iskelet sistemi ağrısı yaygın bir semptom olmamakla birlikte, çalışmamızda yaşam kalitesinin alt grup ölçeklerinden olan ağrı ile kinezyofobi düzeyi ilişkili bulunmuştur.…”
Section: Discussionunclassified